Metabolic undersupport does not lead to obvious performance decrement in elite runners - Kalman, D. S.; Antonio, J. (Sports Nutrition Review Journal, 2004)
The purpose of this study was to describe the energy and macronutrient intake of elite distance runners (National and/or Olympic level). METHODS: A sponsored professional track team was evaluated for anthropometrics, macronutrient and energy intake, total energy and exercise-related energy expenditure. RESULTS: The subjects, all male (n=4), 29 ± 1.87 years old, have a body mass index of 20.3 ± 1.3 kg/m2, consume 2,779 ± 738.7 calories/day with a macronutrient percentages of 54.4 ± 9.1% carbohydrate, 20.3 ± 6% protein and 27.2 ± 8.6% fat. The runners also expended an estimated 2324 ± 483.2 calories daily during exercise training sessions and exercised 973 ± 171.9 minutes per week (or 139 ± 24.5 minutes/day). Estimated total daily energy expenditure for these elite runners is 4239.1 ± 445.99 calories/day with a daily energy deficit of 1460 ± 629.14 calories/day. CONCLUSIONS: It is apparent that within this specific subset of elite distance runners, energy and macronutrient intake is ostensibly inadequate. Because all of these athletes have remained within the top 10 of their respective distance events (5000, 10000m and the marathon) on a National and International level, the apparent daily metabolic deficit does not seem to negatively impact their race performances. However, we do not know if an increase in energy intake as well as an improvement of macronutrient choices would lead to a performance enhancement. Thus, one could speculate that the influence of genetics on exercise ability may compensate for the nutritional inadequacies observed within this subset of elite distance runners.